1991
DOI: 10.1007/bf00994193
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and electroantennogram responses of periplanone analogs

Abstract: The biological activities of synthetic periplanone analogs, including four candidates of periplanone-A (P-A), were evaluated by behavioral and electroantennogram (EAG) assays. Among 16 periplanone analogs, six compounds evoked pheromonal activity from the male American cockroaches. The threshold dosages of these biological active analogs were 10-10(5) times lower than that of the known periplanone mimic, germacrene-D. The conformation required for eliciting the pheromonal activity is discussed in terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Persoons et al (5) identified the first cockroach pheromone component from P. americana and named it periplanone-B. A second, structurally related compound, periplanone-A, was also identified from P. americana (6,7), whereas a similar structure (periplanone-J) has been proposed as the pheromone of P. japonica (8).…”
mentioning
confidence: 99%
“…Persoons et al (5) identified the first cockroach pheromone component from P. americana and named it periplanone-B. A second, structurally related compound, periplanone-A, was also identified from P. americana (6,7), whereas a similar structure (periplanone-J) has been proposed as the pheromone of P. japonica (8).…”
mentioning
confidence: 99%
“…The behavioral assay was done essentially by the same procedure described by us before. 9 ) In this study, the threshold values were defined as the dosage at which significant locomotory activity was observed and more than half the number of the tested insects raised their wings. EAGs were recorded with glass capillary Ag-AgCl electrodes filled with TES Ringer.…”
mentioning
confidence: 99%